A LOOK AT NURMUHAMMAD ANDALIB’S CREATION. - Babadjanova Nazokat (European Journal of Humanities and Educational Advancements, 2024)
This article focuses on some features of the work of the Turkmen poet Nurmuhammad Gharib (Andalib) and analyzes the epic plots included in the writer’s epic “Yusuf and Zulaikha” as a result of the influence of folk art. In addition, the commonality and uniqueness of the elements of the plot, which converge with the epics and stories created among the Turkic peoples based on the plot of “Yusuf and Zulaikha”, are highlighted.